A multi‐technique study of corrosion products at the steel–concrete interface under two exposure conditions. (28th March 2022) - Zhang, Zhidong; Studer, Patrick; Angst, Ueli
Abstract: Steel corrosion can cause serious damage to reinforced concrete structures. This study employed multiple techniques, including SEM/BSE, EDX and Raman spectroscopy, to analyse the distribution and mineral composition of corrosion products (rusts) in corroded reinforced cementitious materials under two conditions, namely, chloride‐induced corrosion and accelerated corrosion in carbonated mortar. Results showed that corrosion products tend to precipitate in large pore spaces close to the steel bar, such as the bleed water zones and voids. Corrosion products initially grew on the walls of these large pores and then the interior was filled with needle‐like products gradually. In carbonated mortar, the length of some corrosion layers matches well the size of the coarse aggregate close to the steel. The main phases that were identified based on Roman spectra are magnetite and maghemite (after samples were exposed to atmosphere). Siderite was observed in carbonated mortars, which is not commonly found under natural conditions.